ANCIENT ARCHITECTURE OF IRRIGATION FACILITIES OF THE ZARAFSHAN OASIS (American Journal of Pedagogical and Educational Research, 2023)
This article is about the relationship to water in history and the culture of water efficiency.Information on the history of hydrology in Central Asia is also covered.Irrigation history of the Lower Zarafshan Valley and similar information is included.